Thai EFL University Students’ Perspectives on Foreign Language Anxiety - Chinpakdee, Muthita (Humanities, Arts and Social Sciences Studies, 2015)
The purposes of this study are to find out the level of foreign language anxiety perceived by Thai EFL learners through identifying their possible causes of foreign language anxiety and determining the potential solutions to minimize their English language learning anxiety. Drawing upon the Foreign Language Classroom Anxiety Scale (FLCAS) and focus group interviews, the findings revealed that Thai EFL learners experienced a high level of anxiety both inside and outside language classroom contexts. Four main possible factors including academic evaluations, negative evaluations, comprehension problems, and teachersrelated factors were found to be contributing factors to Thai EFL learners’ foreign language anxiety. Lastly, suggestions were proposed in order to create low-anxiety foreign language classrooms.